A novel digital workflow for fabricating artificial periodontal ligament using three-dimensional printing flexible resin: A dental technique - Hatem Alqarni; Mohammed A. Alfaifi; Majed S. Altoman; Abdulaziz A. AlHelal; Walaa Magdy Ahmed; Amr Ahmed Azhari; Mathew T. Kattadiyil (Saudi Dental Journal)
The fabrication of periodontal ligament (PDL) models for in vitro dental studies has seen a wide range of techniques and materials being utilized. This paper introduces a novel dental technique that employs a digital workflow for the fabrication of artificial PDL using three-dimensional printing of flexible resin. This innovative approach offers several advantages, including enhanced accuracy and realism in simulating PDL. The digital workflow facilitates a streamlined fabrication process, ensuring efficiency and precision. By presenting this novel technique, this digital approach contributes to the advancement of in vitro dental research, providing researchers with a reliable and realistic model for studying various dental phenomena.